Társadalmi szervezetek, alapítványok a közhasznúság tükrében - Héthy, Eszter (Debreceni Jogi Műhely, 2020)
The Constitution of the Republic of Hungary declares that under the right of association everyone has the right to found organisations – for purposes not prohibited by law – respectively join to them. More and more citizens and legal entities have utilized the possibilities guaranteed by the constitution since the regime change thus, the number of the associations and trusts has been increasing annually. The purpose of this essay is to present the past, the present and the possible future of trusts and non-govermental organizations with a special focusing on the condition of registration of the public benefit of organisations (PBO), and the rules of the management, operation, economic advantages and supervisions of these PBOs.